The Palgrave handbook of German idealism - Altman, Matthew C. (Palgrave handbooks, 2014)
German Idealism is one of the most fruitful and influential movements in the history of philosophy. The Palgrave Handbook of German Idealism covers this era in meticulous detail, with contributions from some of the best scholars in this field, nearly all of which have been specially commissioned for this volume. Chapters set the philosophers and their work in historical context, evaluate the philosophical importance of the four most important idealists (Kant, Fichte, Schelling, and Hegel), and address the many fields of philosophy to which they made the greatest impact, including epistemology,